2019
DOI: 10.3389/fnagi.2019.00115
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning and Multiplex Networks for Accurate Modeling of Brain Age

Abstract: Recent works have extensively investigated the possibility to predict brain aging from T1-weighted MRI brain scans. The main purposes of these studies are the investigation of subject-specific aging mechanisms and the development of accurate models for age prediction. Deviations between predicted and chronological age are known to occur in several neurodegenerative diseases; as a consequence, reaching higher levels of age prediction accuracy is of paramount importance to develop diagnostic tools. In this work,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 57 publications
(61 reference statements)
0
31
0
Order By: Relevance
“…We used linear models in order to facilitate better interpretations. More sophisticated yet complicated models could also have been used to possibly have better predictive power, for example, to have higher prediction accuracy in age prediction [116]. Nevertheless, using a simple linear predictor, we were able to achieve a substantial cross-validated accuracy, which effectively demonstrates the capability of our model in capturing the brain maturation patterns.…”
Section: Limitationsmentioning
confidence: 84%
“…We used linear models in order to facilitate better interpretations. More sophisticated yet complicated models could also have been used to possibly have better predictive power, for example, to have higher prediction accuracy in age prediction [116]. Nevertheless, using a simple linear predictor, we were able to achieve a substantial cross-validated accuracy, which effectively demonstrates the capability of our model in capturing the brain maturation patterns.…”
Section: Limitationsmentioning
confidence: 84%
“…The prediction accuracy that we obtained is in the same range as has been demonstrated by previous studies while using different morphological measures and age prediction methods ( ) [ 22 , 51 , 52 , 53 , 54 , 55 ]. Most of these studies are focused on younger subjects (age years) and reported MAE [ 51 , 52 , 54 , 55 ], while other works showed that the prediction error increases with increasing age with MAE in the same age range of our analysis [ 22 , 53 , 56 ]. Our results seem to confirm such an observation: even though the overall mean prediction errors resulting from random forest age regression for the age covariate harmonization and no harmonization are similar to those reported in literature, all of the models show worse performance for age years.…”
Section: Discussionmentioning
confidence: 98%
“…The success of CNNs in computer vision has led to numerous applications in medical imaging and more recently in age prediction from neuroimaging data (17,(45)(46)(47)(48)(49).…”
Section: Model 3: Six-layer Convolutional Neural Networkmentioning
confidence: 99%